An Analysis on the Sentence Construction in English Textbook and Students’ Narrative Text Writing at Eleventh Grade Students of SMAN 19 Kabupaten Tangerang in Academic Year 2019/2020 - Achmad Fachrurrozy; Irmala Sukendra; Putri Mega Pertiwi (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The aim of this research is to analyze on the sentence construction in English textbook and students’ essay narrative text writing. This research used qualitative methods. The population of this research which consisted of 398 students and then, 36 students from class XI MIA 4 were selected as the sample. The data were collected using students’ essay and seventh texts in English textbook to be analyzed. The researcher analyzed about the sentence construction in all of the texts in English textbook and in students’ essay. Sentence constructions that will be analyzed by the researcher are the five of grammatical tenses. The tenses are simple past tense, past continuous tense, past perfect continuous tense, past perfect tense, and past future tense. After the researcher had analyzed and calculated, the result showed that the total percentage of English textbook and in students’ essay have the same percentage that is 90%. It means that, the students’ can apply sentence construction in their writing and sentence construction in seventh texts in English textbook is better. Key words: Sentence Construction, English Textbook, Writing